"This is not censorship": The BBC and the Broadcasting Ban (1988-1994) - Élodie Gallet (Cahiers du MIMMOC)
The broadcasting ban was in force between 1988 and 1994 in the United Kingdom. It is an example of direct censorship that affected the television and radio coverage of the situation in Northern Ireland. It was introduced when violence was escalating in Northern Ireland and when the broadcasting industry sought to assert its independence from the State by protecting its sources and giving a voice to those identified as the enemies. The notices issued on 19 October 1988 aimed both at calming the violence and at impeding directly the communication operated by the Republicans, in particular by Sinn Féin and the IRA. Thus, the Government used broadcasting, and TV in particular, in an attempt to stifle the voice of its enemies and to legitimise the government’s policy in Northern Ireland in the eyes of the public.While these measures did not radically change the representation of the IRA on TV, they did, however, have the effect of reinforcing the journalists, and the BBC’s self-censorship. They also had the unintended consequence of diverting media attention to other issues such as the links between loyalist paramilitaries and British security forces, or the daily lives of people in Northern Ireland.